2011
DOI: 10.1007/s12028-011-9567-y
|View full text |Cite
|
Sign up to set email alerts
|

Withdrawal of Life-Sustaining Treatment in a Mixed Intensive Care Unit: Most Common in Patients with Catastropic Brain Injury

Abstract: In 83, 7% of patients who die in the mixed ICU life-sustaining treatment is withdrawn. Severe cerebral damage was the leading reason to withdraw life-sustaining treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 30 publications
1
23
1
Order By: Relevance
“…EoL practices in neurological and/or neurosurgical intensive care units (NICU) have been studied by other authors [3032]. Two different single-center studies in NICU found TLDs in 4% and 14% of cases [30, 31].…”
Section: Discussionmentioning
confidence: 99%
“…EoL practices in neurological and/or neurosurgical intensive care units (NICU) have been studied by other authors [3032]. Two different single-center studies in NICU found TLDs in 4% and 14% of cases [30, 31].…”
Section: Discussionmentioning
confidence: 99%
“…Overly pessimistic prognostication and difficulty predicting patient adaptation could lead to an inappropriate increase in withdrawal of life-sustaining therapy in the neuroICU [15][16][17]. Since the majority of patients with severe neurologic injury who die in the ICU do so in the setting of withdrawal of mechanical ventilation, this is an important area for future study [13,14,18]. Although palliative care consultation triggers could expedite and improve the integration of palliative care into the neuroICU, the most efficient and patient-centered model of providing palliative care is not clear.…”
Section: Discussionmentioning
confidence: 99%
“…One potential explanation is that prognostic indices based on several factors in combination may predict outcome with better accuracy in neuro-critical care than in other areas in medicine (54)(55)(56)(57)(58). For patients with congestive heart failure, obstructive bronchitis, cirrhosis, kidney disease or cancer, it is rarely possible to prognosticate with certainty that a chronically ill subject will not survive an acute episode (59).…”
Section: Caregivers Have Equal Responsibility Towards Both the Dying mentioning
confidence: 99%